Pengaruh Keputusan Investasi, Keputusan Pendanaan, Kebijakan Dividen, Dan Good Corporate Governance Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Go Public Yang Terdaftar Di Corporate Governance Perception Index (CGPI) Periode 2010-2013) - Yudoko, Guntur Adi; , Dr. Erma Setiawati, MM.,CA (2017)
This study aims to test empirically the impact ofinvestment decisions, financing decisions, dividend policy, and good corporate governance on firm value. The objects of study are all of go public companies listed in Corporate Governance Perception Index (CGPI) during 2010-2013. Population of this study is the go public companies listed in Corporate Governance Perception Index (CGPI) during 2010-2013.The study used purposive sampling method to collect the sample. Based on certain criteria, there were 45 go public companies that matched with the sample, but from the sample have 2 companies with outlier data. Because the outlier of data, the sample from this study are 43 companies.The analysis of statistic on this study used multiple regression analysis.The result of this study showed that investment decision (PER) has the significant effect on firm value, financing decision (DER) has not the significant effect on firm value, dividend policy (DPR) has the significant effect on firm value, and good corporate governance (GCG) does not have the significant effect on firm value.